Myanmar Spelling Error Classification: An Empirical Study of Tsetlin Machine Techniques - Phyu, Ei Thandar; Thu, Ye Kyaw; Oo, Thazin Myint; Chanlekha, Hutchatai; Supnithi, Thepchai (Journal of Intelligent Informatics and Smart Technology, 2024)
Accurate spelling and grammar checking is fundamental to the development of language tools for Myanmar language. Classifying spelling error types is crucial in spell checkers and other language processing tools because it enables more accurate and context-aware error corrections. This process categorizes spelling errors in written text into distinct types or categories. To address the lack of such resources for Myanmar language, we have developed a spelling corpus containing misspelled words alongside their corrected forms in a parallel structure, paired with a corpus categorizing types of spelling errors. This paper focuses on an observational study of the Tsetlin Machine for Myanmar spelling error type classification, involving comprehensive parameter tuning and a performance comparison with fastText, a state-of-the-art natural language processing model. Our studies indicate that while the Tsetlin Machine achieves comparable results to fastText specifically in the domain of phonetic error classification, it demonstrates lower efficacy in other error classes.